PERBANDINGAN KARAKTERISTIK BISKUIT LIDAH KUCING DENGAN SUBSTITUSI JENIS CANGKANG TELUR YANG BERBEDA - Setianingsih, Annisa; Fajriah Normawati, Zul’aidatul; Amanda Panjaitan1, Dea; Muflihati, Iffah; Suhendriani, Sari; Dwi Ujianti, Rizky Muliani (Jurnal Inovasi Bahan Lokal dan Pemberdayaan Masyarakat, 2022)
Egg shell is the outer layer that protects the contents of the egg, egg shell contains a balanced mineral including calcium, besides being a natural source of calcium that is easily digested and absorbed by the body, therefore egg shells are good to add in making cat tongue biscuits. Biscuits are a type of dry biscuit made from wheat flour, egg whites, caster sugar and margarine. Lidah kucingbiscuits have the characteristics of being shaped like a lidah kucing, thin, has a crunchy texture, brown in color, brittle and has a sweet taste. This study aims to determine the effect of adding various types of eggshell flour to the characteristics of color, moisture content, and ash content of cat's tongue biscuits. The experimental design used was a completely randomized design with treatment of 3 different types of flour, namely chicken egg shell flour, duck egg shell flour, and quail egg shell flour. The test results showed that the highest water content and ash content were produced by the addition of chicken egg shell flour and quail egg shell with a water content of 3.30% and an ash content of 5.7%. The organoleptik test of Biscuit Lidah Kucing that is acceptable and preferred by the panelis the treatment of chicken flour.